Antimicrobial activity of sulfonamides containing 5-chloro-2-hydroxybenzaldehyde and 5-chloro-2-hydroxybenzoic acid scaffold - Krátký, Martin; Vinšová, Jarmila; Volková, Marie; Buchta, Vladimír; Trejtnar, František; Stolaříková, Jiřina (European journal of medicinal chemistry, 2012)
A series of novel sulfonamides containing 5-chloro-2-hydroxybenzaldehyde or 5-chloro-2-hydroxybenzoic acid scaffolds were designed, synthesized and characterized by IR, (1)H NMR and (13)C NMR. All ten target synthesized derivatives and starting sulfonamides were evaluated in vitro for the activity against Gram-positive and Gram-negative bacteria, fungi, Mycobacterium tuberculosis, Mycobacterium avium and Mycobacterium kansasii. The most active compound against methicillin-sensitive and methicillin-resistant Staphyloccoccus aureus was 5-chloro-N-{4-[N-(4,6-dimethylpyrimidin-2-yl)sulfamoyl]phenyl}-2-hydroxybenzamide with MIC 15.62-31.25 μmol/L. 4-Amino-N-(thiazol-2-yl)benzenesulfonamide and 4-(5-chloro-2-hydroxybenzylideneamino)-N-(thiazol-2-yl)benzenesulfonamide have shown the best activity against M. kansasii at the concentrations of 1-4 μmol/L. The efficacy against other strains was weaker and the studied derivatives exhibited almost none antifungal potency.
Keywords: mikrobiální testy citlivosti; houby; Thiazoles; thiazoly; Molecular Structure; Structure-Activity Relationship; antiinfekční látky; Anti-Infective Agents; Sulfonamides; Spectrophotometry, Infrared; Fungi; magnetická rezonanční spektroskopie; molekulární struktura; Benzamides; Microbial Sensitivity Tests; Bacteria; benzamidy; sulfonamidy; spektrofotometrie infračervená; vztahy mezi strukturou a aktivitou; Magnetic Resonance Spectroscopy